Infectious viruses for the biological control of rice-field rats : rat cytomegalovirus (RCMV) as a suitable candidate for the development of immunocontraceptive vaccines. - Mohd Lila, Mohd Azmi; Lai, Kit Yee; Abdul Rahman, Sheikh Omar; Smith, A. L.; Lam, Y. M. (1999)
A serologic survey of viruses infecting rice-field rats (Rattus argentiventer)in Malaysia was conducted in five different geographic locations. Results indicate that approximately 50% of the rice-field rats were positive for rat crytomegalovirus (RCMV). A lower prevalence rate has been demonstrated fro coronavirus, adenovirus, new rat parvovirus, conventional parvovirus and Theiler's virus. None of the serum samples tested positive for lymphocytic choriomeningitis virus (LCMV), vaccinia virus, Hantaan virus, Seoul virus, pneumonia virus and Sendai virus. RCMV was highly prevalent at different sampling locations. Two different RCMVs have been isolated from the rats. These viruses have been extensively characterised and compared with established RCMV strains of Rattus norvegicus. The new RCMV strains designated RCMV-Sg and RCMV-Kn were different at molecular level but serelogically related. Based on their biological and molcecular characteristics it is likely that the virus could be used as a vehicle to carry immunocontraceptive genes.